Synthesis of 3‐Selenylindoles under Ecofriendly Conditions. Issue 23 (15th July 2015) - Ferreira, Natasha L.; Azeredo, Juliano B.; Fiorentin, Breno L.; Braga, Antonio L.
Abstract: The preparation of biologically relevant 3‐selenylindoles by a greener protocol by using a catalytic amount of K2 CO3 and ethanol as a biosolvent in a system open to air was explored. Through this easy approach, 3‐selenylindoles with different functionalities were obtained in good yields by a radical pathway. Abstract : The synthesis of biologically relevant 3‐selenylindoles by using a catalytic amount of K2 CO3 and ethanol as an ecofriendly reaction medium in a system open to air is described. Through this approach, a series of 3‐selenylindoles are obtained in good yields by a radical pathway.